Percolation transition and physical properties of Bi1-xSbx solid solutions at low Bi concentration - Rogacheva, E. I.; Doroshenko, A. N.; Khramova, T. I.; Nashchekina, O. N.; Fedorov, A. G.; Mateychenko, P. V. (Elsevier Ltd, 2020)
The dependences of microhardness H, electrical conductivity σ, charge carrier mobility μH, the Seebeck coefficient S, and thermoelectric power factor P = S2σ on the composition of Bi1-xSbx solid solutions in the vicinity of pure Sb (x = 1.0–0.975) were obtained. In the range of x = 0.9925–0.9875, an anomalous decrease in H and S and increase in σ and μH with increasing Bi concentration were observed. For all the alloys, the dependences of H on the load on an indenter G were plotted. It was found that the H(G) dependences for samples with x smaller than ~ 0.99 and for samples with x exceeding 0.99, exhibit different behavior. The results obtained are interpreted on the basis of our assumption about the existence of a percolation-type phase transition from impurity discontinuum to impurity continuum that occurs in any solid solution.
Keywords: alloys; mechanical properties; transport properties; phase transition; critical phenomena